2012
DOI: 10.1080/08941920.2011.603141
|View full text |Cite
|
Sign up to set email alerts
|

Conservation NGOs in Madang, Papua New Guinea: Understanding Community and Donor Expectations

Abstract: This article presents a case study from Madang, Papua New Guinea, to illustrate how the priorities of an international environmental nongovernmental organization (NGO) aligned with donor expectations and diverged from the expressed conservation preferences of local residents for management and enforcement. Analysis of data from semistructured interviews with local residents in three villages identified three local community expectations of a Madang NGO: serving as an alternative to the state; providing materia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 24 publications
1
23
0
Order By: Relevance
“…Such a community-level approach is also culturally more acceptable as it can be applied with consideration to individual differences in culture and geography between villages and communities. Applications of this 'bottom up 'approach in commercial (O'Brien and Ponting: 2013) and conservation (Benson, 2012;Ancrenaz, 2007) contexts in PNG have proved successful. Even when applied to the 'amenity poor remote' Waluma community, where external assistance for a conservation project was limited solely to an advisory capacity, this approach still proved successful (Sakata and Prideaux, 2013, p. 880).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such a community-level approach is also culturally more acceptable as it can be applied with consideration to individual differences in culture and geography between villages and communities. Applications of this 'bottom up 'approach in commercial (O'Brien and Ponting: 2013) and conservation (Benson, 2012;Ancrenaz, 2007) contexts in PNG have proved successful. Even when applied to the 'amenity poor remote' Waluma community, where external assistance for a conservation project was limited solely to an advisory capacity, this approach still proved successful (Sakata and Prideaux, 2013, p. 880).…”
Section: Discussionmentioning
confidence: 99%
“…Until attitudes change, a challenge at community level would be identifying projects, that create social value in a village, where women's willingness to engage in social development could be harnessed without trespassing on men's territory. A challenge for NGOs and churches in initiating projects would be to earn community support (Bond et al, 2015) without raising community expectations of material benefits (Benson, 2012). A partner agency would need to 'demonstrate the effectiveness' of a project in improving lives (Stilltoe, 2010), to gain the support of men and thereby community acceptance.…”
Section: Discussionmentioning
confidence: 99%
“…In the particular case of Rapa Nui, the presence of BINGOs in the island has divided the community into those who support the BINGOs' conservation plans and those who want to pursue their own process and conservation proposals. The mismatch between BINGOs and community objectives has been described in Madang, Papua New Guinea, where BINGOs prioritized donor objectives in conservation above the local communities' needs (Benson, ). It has also been suggested that some NGOs may have ideological views that may not be acceptable to the community or the government (Pomeroy et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…Research on the social issues of conservation has been at the centre of scientific and policy discussions for a long time; it is argued that this aspect provides a promising path to understand power asymmetries, and identify conflict resolution and effective conservation engagements (Lund and Bluwstein 2018). Numerous participatory and decentralized approaches have been introduced in protected area management (Ribot 1999(Ribot , 2002Galvin and Haller 2008;Benson 2012;, including the co-management approach. Having been applied for over two decades in several contexts, the co-management concept is viewed as a power and responsibility sharing process, which is geared towards improving protected area management efforts (Frame et al 2004;Armitage et al 2008;Schultz et al 2011;Plummer et al 2017a).…”
Section: Introductionmentioning
confidence: 99%